Implementasi Sistem Rujukan Terintegrasi (Sisrute) di RSUD Dr. Soedarso - Annisa Pirlaily Pazriani; Cau Kim Jiu; Lidia Hastuti (Universitas Malahayati Lampung, 2026)
ABSTRACT The implementation of health referrals in Indonesia still faces obstacles such as lack of coordination between health facilities and suboptimal use of technology. RSUD Dr. Soedarso has implemented the Integrated Referral System (SISRUTE), yet it still encounters challenges including